A method for preparing flaky hollow fiber aerogel
By preparing flaky hollow fiber aerogel, using electrospinning technology and APTES surface modification, the problems of low adsorption and insufficient hydrophobicity of existing oil-water separation materials are solved, and efficient oil-water separation effect is achieved.
Patent Information
- Application Number
- CN202310188634.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-01
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-03-01
AI Technical Summary
The existing oil-water separation materials have low adsorption and insufficient hydrophobicity, resulting in low oil-water separation efficiency.
By preparing scaly hollow fiber aerogel, a scale-like structure imitating shark skin is prepared by electrospinning technology, and hydrophobicity is improved through APTES surface modification.
The oil-water separation efficiency has been significantly improved, the effective filling area per unit volume is large, the directional arrangement of scale fibers reduces the resistance to water passage, and the composite fiber aerogel has good oleophilic and hydrophobic properties.
Smart Images

Figure CN116272899B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of oil-water separation material preparation, and relates to a method for preparing flaky hollow fiber aerogel. Background Art
[0002] Water shortage and pollution have a wide impact on the sustainable development of industrial and social activities, and are one of the most severe global challenges facing mankind in the 21st century. A large amount of oily wastewater generated by industries such as petroleum, chemical, steel, and food processing is a major source of pollution. Oil-water separation is of great significance to oil recovery, water resource reuse, and environmental protection. At present, physical, chemical, and biological methods have been used to separate oil-water mixtures. Among them, membrane separation technology is a high-tech technology with great development prospects in recent years. It has unique characteristics such as strong adaptability, good selectivity, simple preparation process, energy saving, no phase change, and no secondary pollution. With the continuous enhancement of human environmental protection awareness and the promotion and application of membrane technology, membrane technology has been widely used in the treatment of various industrial wastewaters, municipal sewage, and domestic sewage.
[0003] Hollow fiber membrane is one of the main forms of separation membrane, with large effective filling area per unit volume, high separation efficiency, easy cleaning, simple structure, convenient operation and other characteristics. In recent years, nanofiber porous membrane prepared by electrospinning technology has morphological characteristics such as fine fiber fineness, large surface area, high porosity, as well as good mechanical strength, light weight and easy functionalization, and has attracted much attention from researchers in various countries in the application research in the field of membrane separation. However, in actual use, its two-dimensional structure has problems such as less adsorption and low adsorption efficiency compared with the three-dimensional structure. At the same time, it will be wetted by water due to insufficient hydrophobicity, thus affecting the oil-water separation time and efficiency. Therefore, improving the adsorption capacity and hydrophobicity has become an urgent problem to be solved.
[0004] Wang et al. (Xueyan Wang, Zhong Liu, et al. Ultralight and multifunctional PVDF / SiO2@GO nanofibrous aerogel for efficient harshenvironmental oil-waterseparation and crude oil absorption[J]. Carbon, 2022, 193: 77-87.) prepared PVDF / SiO2 nanofibers by electrospinning, and then prepared PVDF / SiO2@GO nanoaerogel by freeze-drying, which has good oil-water separation performance. However, GO is amphiphilic and hydrophilic, and can be wetted by water while adsorbing oil, which makes PVDF / SiO2@GO nanoaerogel insufficiently hydrophobic and reduces the oil-water separation efficiency.
[0005] The Chinese patent application "A polyvinylidene fluoride hollow fiber membrane and its preparation method" (application number: 202111062286, publication number: CN114053883A, publication date: 2022.02.18) discloses a polyvinylidene fluoride hollow fiber membrane and its preparation method. The hollow fiber membrane is made of polyvinylidene fluoride (PVDF) as raw material. The porous structure prepared under the action of a diluent significantly increases the effective filtration surface area of the hollow fiber membrane, so that the hollow fiber membrane has a large filtration flux and a good retention effect. However, it only increases the specific surface area and hydrophobicity by preparing a porous surface structure to change the surface structure. The oil absorption capacity is small and the hydrophobicity is not greatly improved, and the oil-water separation effect is poor.
[0006] Chinese patent application "A method for preparing an oil-water separation fiber membrane" (application number: 201610429517.1, publication number: CN105908364A, publication date: 2016.08.31) discloses a method for preparing an oil-water separation fiber membrane, in which hydrophobic nano-silica powder is added to a polymer spinning solution, and a fiber membrane is obtained by electrospinning, which has a certain oil-water separation effect. However, because this method has the problems of low specific surface area and uneven distribution of hydrophobic nano-silica, the obtained membrane has insufficient oil absorption capacity and hydrophobicity, and the oil-water separation effect is poor.
[0007] The Chinese patent application "Preparation method of modified Caragana fiber aerogel and modified Caragana fiber aerogel" (application number: 202211190986.4, publication number: CN115403821A, publication date: 2022.11.29) discloses a preparation method of modified Caragana fiber aerogel, and the modified Caragana fiber aerogel is obtained by surface activation and freeze-drying of Caragana powder; it can better adsorb a variety of light oils and heavy oils in water and has an oil-water separation effect, but it has the disadvantage of poor hydrophobicity and poor separation effect. Summary of the invention
[0008] The purpose of the present invention is to provide a method for preparing flaky hollow fiber aerogel, which solves the problems of low adsorption capacity and insufficient hydrophobicity of oil-water separation materials in the prior art.
[0009] The technical solution adopted by the present invention is a method for preparing flaky hollow fiber aerogel, which is specifically implemented according to the following steps:
[0010] Step 1, preparation of hydroxylated monolayer nanosheets:
[0011] Melamine and boric acid (mass ratio 3:1) were dissolved in water in proportion by heating at 90°C in a water bath, and then dried and calcined at 1200°C for 2h in a N2 atmosphere to obtain boron nitride; BN was dispersed in a mixed solution of isopropanol and deionized water (volume ratio 1:1), and ultrasonically treated by an ultrasonic cell disruptor, and the obtained dispersion was centrifuged and dried to obtain a monolayer hydroxylated BN nanosheet;
[0012] Step 2, prepare the outer shell and inner core spinning solution:
[0013] The nanosheets obtained in step 1 are added to a polymer solution, which is composed of the following substances by mass percentage: 4% to 10% of nanosheets, 10% to 20% of PVDF, 50% to 66% of solvent, and 20% of PVP pore former, and the sum of the above components is 100%, to prepare a shell spinning solution;
[0014] Step 3, preparation of scaly hollow fibers:
[0015] The outer shell spinning solution obtained in step 2 is placed in a shell layer propulsion pump, and the inner core spinning solution is placed in a core layer propulsion pump, and coaxial electrospinning is performed to obtain flaky hollow fibers; and the flaky hollow oriented fibers are collected using a mold filled with an ethanol solution;
[0016] Step 4, hydrophobic modification of aerogel:
[0017] The biomimetic aerogel obtained by freeze-drying the oriented fibers collected in step 3 is then placed in a 20% to 30% APTES hydrolyzed ethanol aqueous solution for heating and soaking at a temperature of 70° C. to 80° C. for 5 h to 6 h. After draining, the aerogel is dried at room temperature.
[0018] Preferably, the ultrasonic power is 10 to 20 W, and the ultrasonic time is 10 to 20 hours.
[0019] Preferably, the solvent is any one of tetrahydrofuran (THF) and N,N-dimethylformamide (DMF).
[0020] Preferably, the inner core spinning solution in step 3 is 45% alcohol aqueous solution, glycerol, and 45% DMF aqueous solution.
[0021] Preferably, the electrospinning parameters in step 3 are a spinning voltage of 15 to 20 kV, a receiving distance of 10 to 20 cm, a spinning temperature of 20°C to 30°C, a humidity of 10% to 30%, an outer shell spinning solution propulsion speed of 0.2 mL / h to 0.5 mL / h, and an inner core spinning solution propulsion speed of 0.15 mL / h to 0.3 mL / h.
[0022] Preferably, in step 4, a container containing 30% ethanol solution is used to receive the fibers, the oriented fiber collection time is 2 hours to 6 hours, the freezing temperature is -20°C to -40°C, and the drying time is 5 hours to 8 hours.
[0023] The beneficial effects of the present invention are: a method for preparing a scaly hollow fiber aerogel, which makes full use of the micro-nano high roughness structure produced by the shark skin scaly structure prepared by electrospinning, and exhibits excellent oil-water separation efficiency and adsorption capacity. The hollow fiber has a large effective filling area per unit volume, and the bionic structure of the directional arrangement of the scaly fibers greatly reduces the resistance of water passing through. At the same time, the composite fiber aerogel greatly improves the oil-water separation efficiency due to its three-dimensional structure and its lipophilic and hydrophobic properties, and has broad application prospects in the fields of sewage treatment, oil-water separation, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic diagram of the morphology of the oil-water separation aerogel prepared by the present invention. DETAILED DESCRIPTION
[0025] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments, but the following embodiments are only preferred embodiments of the present invention, not all. Based on the embodiments in the implementation mode, other embodiments obtained by those skilled in the art without creative work all belong to the protection scope of the present invention. The experimental methods in the following embodiments, unless otherwise specified, are conventional methods, and the materials, reagents, etc. used in the following embodiments, unless otherwise specified, can all be obtained from commercial channels.
[0026] Embodiment one:
[0027] Preparation of biomimetic fiber aerogel
[0028] Step 1. Melamine and boric acid (mass ratio 3:1) are dissolved in water in proportion by heating at 90°C in a water bath, and then dried and calcined at 1200°C for 2h in a N2 atmosphere to obtain boron nitride (BN); BN is dispersed in a mixed solution of isopropanol and deionized water (volume ratio 1:1), and ultrasonically treated by an ultrasonic cell disruptor with an ultrasonic power of 20W and an ultrasonic time of 10h. The obtained dispersion is centrifuged and dried to obtain a monolayer hydroxylated BN nanosheet, and then the following main raw materials are distributed according to mass percentage: PVDF 10%, BN nanosheet 4%, organic solvent DMF 66%, porogen PVP 20% to obtain a shell spinning solution; glycerol is used as the core spinning solution;
[0029] Step 2. Place the outer shell spinning solution and the inner core spinning solution into a propulsion pump, adjust the electrospinning voltage to 20 kV, the receiving distance to 20 cm, the spinning temperature to 20 ° C, the humidity to 10%, the outer shell spinning solution propulsion speed to 0.2 mL / h, and the inner core spinning solution propulsion speed to 0.15 mL / h, and perform coaxial electrospinning to obtain flaky hollow fibers;
[0030] Step 3. The fiber was received by a spinning wheel placed in a mold containing a 30% ethanol aqueous solution for 2 hours, and the composite fiber aerogel was obtained by freeze drying, with the freezing temperature being -20°C and the drying time being 5 hours. The obtained aerogel was placed in a 30% APTES hydrolyzed ethanol aqueous solution and heated and soaked, with the heating temperature being 70°C and the heating time being 6 hours. After draining, the aerogel was dried at room temperature to obtain the biomimetic aerogel.
[0031] Embodiment two:
[0032] Preparation of biomimetic fiber aerogel
[0033] Step 1. Melamine and boric acid (mass ratio 3:1) are dissolved in water in proportion by heating at 90°C in a water bath, dried and calcined at 1200°C for 2h in a N2 atmosphere to obtain boron nitride (BN). BN is dispersed in a mixed solution of isopropanol and deionized water (volume ratio 1:1) and ultrasonically treated by an ultrasonic cell disruptor, with an ultrasonic power of 17W and an ultrasonic time of 13h. The obtained dispersion is centrifuged and dried to obtain a monolayer hydroxylated BN nanosheet, and then the following main raw materials are distributed by mass percentage: PVDF 15%, BN nanosheet 6%, organic solvent THF 49%, porogen PVP 20% to obtain the outer shell spinning solution; then deglycerol is used as the inner core spinning solution;
[0034] Step 2. Place the outer shell spinning solution and the inner core spinning solution into a propulsion pump, adjust the electrospinning voltage to 15 kV, the receiving distance to 10 cm, the spinning temperature to 25 ° C, the humidity to 20%, the outer shell spinning solution propulsion speed to 0.5 mL / h, and the inner core spinning solution propulsion speed to 0.3 mL / h, and perform coaxial electrospinning to obtain flaky hollow fibers;
[0035] Step 3. The fiber was received by a spinning wheel placed in a mold containing a 30% ethanol aqueous solution for 6 hours, and the composite fiber aerogel was obtained by freeze drying, with the freezing temperature being -40°C and the drying time being 8 hours; the obtained aerogel was placed in a 30% APTES hydrolyzed ethanol aqueous solution and heated and soaked, with the heating temperature being 80°C and the heating time being 5 hours. After draining, the aerogel was dried at room temperature to obtain the biomimetic aerogel.
[0036] Embodiment three:
[0037] Preparation of biomimetic fiber aerogel
[0038] Step 1. Melamine and boric acid (mass ratio 3:1) are dissolved in water in proportion by heating at 90°C in a water bath, dried and calcined at 1200°C for 2h in a N2 atmosphere to obtain boron nitride (BN). BN is dispersed in a mixed solution of isopropanol and deionized water (volume ratio 1:1) and ultrasonically treated by an ultrasonic cell disruptor, with an ultrasonic power of 15W and an ultrasonic time of 17h. The obtained dispersion is centrifuged and dried to obtain a monolayer hydroxylated BN nanosheet, and then the following main raw materials are distributed by mass percentage: PVDF 20%, BN nanosheet 10%, organic solvent DMF 50%, porogen PVP 20% to obtain the outer shell spinning solution; then 45% ethanol is used as the inner core spinning solution;
[0039] Step 2. Place the outer shell spinning solution and the inner core spinning solution into a propulsion pump, adjust the electrospinning voltage to 18 kV, the receiving distance to 15 cm, the spinning temperature to 30 ° C, the humidity to 30%, the outer shell spinning solution propulsion speed to 0.3 mL / h, and the inner core spinning solution propulsion speed to 0.2 mL / h, and perform coaxial electrospinning to obtain flaky hollow fibers;
[0040] Step 3. The fiber was received by a spinning wheel placed in a mold containing a 30% ethanol aqueous solution for 4 hours, and the composite fiber aerogel was obtained by freeze drying, with the freezing temperature being -30°C and the drying time being 6 hours; the obtained aerogel was placed in a 25% APTES hydrolyzed ethanol aqueous solution and heated and soaked, with the heating temperature being 75°C and the heating time being 6 hours. After draining, the aerogel was dried at room temperature to obtain the biomimetic aerogel.
[0041] Embodiment four:
[0042] Preparation of biomimetic fiber aerogel
[0043] Step 1. Melamine and boric acid (mass ratio 3:1) are dissolved in water in proportion by heating at 90°C in a water bath, dried and calcined at 1200°C for 2h in a N2 atmosphere to obtain boron nitride (BN). BN is dispersed in a mixed solution of isopropanol and deionized water (volume ratio 1:1) and ultrasonically treated by an ultrasonic cell disruptor, with an ultrasonic power of 10W and an ultrasonic time of 20h. The obtained dispersion is centrifuged and dried to obtain a monolayer hydroxylated BN nanosheet, and then the following main raw materials are distributed by mass percentage: PVDF 20%, BN nanosheet 8%, organic solvent THF 52%, porogen PVP 20% to obtain the outer shell spinning solution; then 45% DMF is used as the inner core spinning solution;
[0044] Step 2. Place the outer shell spinning solution and the inner core spinning solution into a propulsion pump, adjust the electrospinning voltage to 15 kV, the receiving distance to 15 cm, the spinning temperature to 20 ° C, the humidity to 10%, the outer shell spinning solution propulsion speed to 0.4 mL / h, and the inner core spinning solution propulsion speed to 0.3 mL / h, and perform coaxial electrospinning to obtain flaky hollow fibers;
[0045] Step 3. The fiber was received by a spinning wheel placed in a mold containing a 30% ethanol aqueous solution for 5 hours, and the composite fiber aerogel was obtained by freeze drying, the freezing temperature was -30°C, and the drying time was 7 hours; the obtained aerogel was placed in a 20% APTES hydrolyzed ethanol aqueous solution and heated and soaked, the heating temperature was 75°C, and the heating time was 5.5 hours. After draining, the aerogel was dried at room temperature to obtain the biomimetic aerogel.
[0046] The present invention adjusts the number of layers and aspect ratio of BN nanosheets by controlling ultrasonic power and time, so that they are evenly dispersed in PVDF; by controlling the content of BN nanosheets, they are effectively exposed on the surface of hollow fibers, and their lipophilic and hydrophobic properties are used to obtain the oil-water separation effect. In this process, the bionic structure of scaly fibers with directional arrangement constructed by controlling the propulsion speed of the internal and external spinning solutions can also greatly reduce the resistance when water passes through, and improve the oil-water separation efficiency; the hollow fiber constructed by coaxial electrospinning has a higher specific surface area, increases the filtration flux and adsorption capacity, improves the oil-water separation efficiency, makes it more durable, and can be recycled more times; APTES is used for surface modification to further improve its hydrophobic properties and increase the continuous separation time of oil and water.
[0047] The present invention prepares a composite fiber aerogel with high hydrophobicity and specific surface area through coaxial electrospinning, and makes full use of the micro-nano high roughness structure produced by the shark skin scale-like structure prepared by electrospinning. The hollow fiber has a large effective filling area per unit volume, and the bionic structure of the scale fiber with directional arrangement greatly reduces the resistance when water passes through. At the same time, the composite fiber aerogel greatly improves the oil-water separation efficiency due to its three-dimensional structure and its oleophilic and hydrophobic properties, and has broad application prospects in the fields of sewage treatment, oil-water separation, etc.
[0048] Table 1 is a comparison of the diameter, oil-water separation rate and water contact angle of the PVDF / BN composite fiber aerogel, PVDF / BN@GO fiber and conventional PVDF fiber obtained in Example 1. As can be seen from Table 1, the fiber diameter in the PVDF / BN composite membrane fiber aerogel is in the middle, but its oil-water separation rate reaches 99.9%, and its water contact angle reaches 163°. This is because the BN nanosheets are exposed on the surface and the BN nanosheets are evenly distributed, giving full play to the hydrophobic effect of the BN nanosheets. At the same time, the siliconization modification also improves the hydrophobicity. The PVDF / BN@GO nano aerogel coaxial fiber has the largest diameter, but due to the composite of PVDF and BN materials, the interface between the two effectively increases the roughness and improves its hydrophobic efficiency, so its oil-water separation effect is better than that of conventional PVDF fibers.
[0049] Table 1 Comparison of diameter, oil-water separation rate and hydrophilic angle of composite fiber, PVDF-BN@GO composite fiber and conventional PVDF fiber in Example 1
[0050]
[0051] Figure 1 This is a schematic diagram of the bionic structure of the aerogel prepared by the present invention. The BN nanosheets are arranged in a directional manner to form a scale-like structure, which greatly reduces the water resistance. At the same time, after coaxial electrospinning, the hydrophobic BN nanosheets are evenly distributed on the surface of the PVDF fiber, and the combination of the two improves the hydrophobicity.
[0052] The embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited thereto, and various changes can be made within the knowledge scope of technicians in the relevant technical field without departing from the purpose of the present invention.
Claims
1. A method for preparing a scaly hollow fiber aerogel, characterized in that: The specific steps are as follows: Step 1, preparation of hydroxylated monolayer nanosheets: Melamine and boric acid in a mass ratio of 3:1 were dissolved in water by heating at 90°C in a water bath, dried, and then sintered at 1200°C for 2h in a N2 atmosphere to obtain boron nitride; BN was dispersed in a mixed solution of isopropanol and deionized water in a volume ratio of 1:1, and ultrasonically treated by an ultrasonic cell disruptor, and the obtained dispersion was centrifuged and dried to obtain a monolayer hydroxylated BN nanosheet; Step 2, prepare the outer shell and inner core spinning solution: The nanosheets obtained in step 1 are added to a polymer solution, which is composed of the following substances by mass percentage: 4% to 10% nanosheets, 10% to 20% PVDF, 50% to 66% solvent, and 20% PVP pore former, and the sum of the above components is 100%, to prepare a shell spinning solution; the core spinning solution is 45% alcohol aqueous solution, glycerol, and 45% DMF aqueous solution; Step 3, preparation of scaly hollow fibers: The outer shell spinning solution obtained in step 2 is placed in a shell layer propulsion pump, and the inner core spinning solution is placed in a core layer propulsion pump, and coaxial electrospinning is performed to obtain flaky hollow fibers; and the flaky hollow oriented fibers are collected using a mold filled with an ethanol solution; Step 4, hydrophobic modification of aerogel: The biomimetic aerogel obtained by freeze-drying the oriented fibers collected in step 3 is then placed in a 20% to 30% APTES hydrolyzed ethanol aqueous solution for heating and soaking at a temperature of 70° C. to 80° C. for 5 h to 6 h. After draining, the aerogel is dried at room temperature.
2. The method for preparing a scaly hollow fiber aerogel according to claim 1, characterized in that The ultrasonic power is 10-20W, and the ultrasonic time is 10h-20h.
3. The method for preparing a scaly hollow fiber aerogel according to claim 1, characterized in that: The solvent is any one of tetrahydrofuran (THF) and N,N-dimethylformamide (DMF).
4. The method for preparing a scaly hollow fiber aerogel according to claim 1, characterized in that: The electrospinning parameters in step 3 are: spinning voltage of 15-20 kV, receiving distance of 10-20 cm, spinning temperature of 20°C-30°C, humidity of 10%-30%, outer shell spinning solution propulsion speed of 0.2 mL / h-0.5 mL / h, and inner core spinning solution propulsion speed of 0.15 mL / h-0.3 mL / h.
5. The method for preparing a scaly hollow fiber aerogel according to claim 1, characterized in that: In step 4, a container containing 30% ethanol solution is used to receive the fibers. The oriented fiber collection time is 2 hours to 6 hours, the freezing temperature is -20°C to -40°C, and the drying time is 5 hours to 8 hours.
Citation Information
Patent Citations
Oil-water separation fiber membrane
CN105908364A
Polyvinylidene fluoride hollow fiber membrane and preparation method thereof
CN114053883A
A polyvinylidene fluoride hollow fiber membrane and its preparation method
CN114053883B
Preparation method of modified caragana microphylla fiber aerogel and modified caragana microphylla fiber aerogel
CN115403821A
Preparation method of modified Caragana korshinskii fiber aerogel and modified Caragana korshinskii fiber aerogel
CN115403821B